Recent Progress and Development of Small Molecule Kinase Inhibitors for the Treatment of Breast Cancer - Das, Debasis; Hong, Jian (Current Enzyme Inhibition, 2020)
Breast cancer, the most common health burden to women globally, is considered a major cause of death for women every year. Many signal transduction pathways can cause breast cancer. The kinase inhibitors can interrupt the signaling pathways, minimize tumor growth and consequently cure the disease. The scientists have discovered many kinase inhibitors as targeted drugs for breast cancer. In recent years, the inhibitors of EGFR, HER2, VEGFR, PI3K, CDK4/6, PARP and hormone receptor have been studied well for curing breast cancer. The FDA has approved a few kinase drugs such as trastuzumab, lapatinib, neratinib, palbociclib, abemaciclib, alpelisib to treat breast cancer recently. In this review, we summarized the latest development of kinase inhibitors as breast cancer therapy.
Keywords: PI3K